알루미늄 저온 확산코팅의 속도론적 고찰 및 확산코팅법으로 알루미나이드 코팅 및 전처리 산화된 Haynes230 합금의 내삭마특성 - 김민석; Min Seok Kim; 박진수; Jin Soo Park; 손영일; Young Il Son; 박준식; Joon Sik Park (대한금속·재료학회지, 53(10), 2015)
Aluminim pack cementation coatings on Haynes 230 alloys have been developed between 500 and 600 ℃. A single Al3Ni layer was coated on the alloys. The activation energy for growth rate of the coated layer thickness was estimated as 63.1 kJ / mol in the examined temperature range. In order to examine the degradation behaviors, the alloys were subjected to high temperature flame via an LPG / O2 gas torch. In order to test the degradation behaviors, uncoated alloys, coated alloys and oxidized following coated alloys have been prepared. The uncoated Haynes 230 alloys exhibited a weight loss during the torch tests due to the sublimation of chromium oxide on the surface, and the coated allo specimen showed an surface melting due to low melting temperature of the coating layer. However, the coated with oxidation - treated Haynes 230 alloys maintained the original weight due to the presence of an surface in-situalumina layer. The coated microstructures and related coating kinetics are discussed in terms of structural identification and weight changes.